DESIGN OF AUTOMATIC DRIP IRRIGATION BASED ON CHANGE OF SOIL WATER CONTENT USING ARDUINO NANO MICROCONTROLLER - Pranata, Rendy (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Formerly, most of Indonesian farmers only used a timer in an effort to set up drip irrigation scheduling. This method is less effective in providing irrigation according to crop water requirement because it is only able to arrange the provision of irrigation basedon a predetermined time interval only, so that the excess or lack ofwater can’t be controlled. This research makes an instrument which is able to overcome these problems, that is by designing an automatic control systemonregulating the provision of irrigationwater in drip irrigation by using amicrocontroller thatworks based onchange of soilwater content. The parameters observed inthis studyare the change of soilwater content, irrigationflowrate, bulk density of soil, and dropper flowuniformity. This study uses three types of growingmedium, i.e. sand, red-yellowpodzolic soil, andmix soil with organic nitrofosfat fertilizer. Calibration tests showed a linear function, for sandmedium y = – 0.23x + 46.96 with percent error ± 5.22%, for red-yellowpodzolic soil andmix soilwith organic nitrofosfat fertilizermediumy = – 0.71x + 104.07with percent error ± 2.92%. The results showed that the automatic control system is able to work well, i.e. turn on the pump when soilwater content drops belowthe criticalwater contentand turnoff the pumpwhen soilwater content rises over the field capacity.